MOBILE ASSISTED LANGUAGE LEARNING IN THE CONTEXT OF COMMUNICATIVE CLASSROOM PRACTICES - Justin Pool, (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
This paper presents a mixed-methods approach to researching the viability of supplementing mobile-assisted language learning (MALL) apps focusing on receptive skills with a course curriculum that emphasizes meaningful communication, mitigation of error-aversion tendencies, cultural awareness, and presentation skills. Adult language learners working for a company were assigned fifty units of the online mobile assisted language learning application, ReallyEnglish, while concurrently taking weekly hour-long lessons that focused on meaningful communication, mitigation of error-aversion tendencies, cultural awareness, and presentation skills. Many researchers have lamented the fact that most MALL applications do not take full advantage of technological affordances to create opportunities for learners to use their devices as tools of interaction. Instead, apps that focus on receptive skills including vocabulary memorization and grammatical rules are more popular. This paper acknowledges that creating more apps focusing on productive skills is necessary but focuses on how to create a robust curriculum surrounding such receptive-skills apps. Learners improved as shown by standardized test scores, learner reflection, and surveys.